OPTIMASI TANAH NAPA SEBAGAI ADSORBEN ION LOGAM Cd (II) - Atina Khairat; Mawardi Mawardi; Hary Sanjaya (Departemen Kimia FMIPA UNP, 2013)
The effort of handing waste which containing heavy metals examined continuesly, once of effort is adsorption method. In the research, examined about optimum condition determinating of metal ion Cd (II) adsorption by Napa soil adsorption from Solok The Aripan’s area. The napa containts silica 70,979 % and alumina 20,748 %, the amount of silica and alumina in napa almost equals it’s concentration with natural zeolite. The purpose of research is to determine the effect of napa maximum adsorption capacity on metal ions Cd (II), as well as the effect of initial concentration solution, pH solution, particle size of adsorbent, heating temperature adsorbent and flow rate eluent. The research was conducted in two phases, that is the preparation and conduct of the examined. The preparation stage includes the prepare of the tools, materials and samples. The implementation stage begins with a preparation of samples, then used it as the metal ion adsorbents Cd (II). Measurement of the ions Cd (II) concentration conducted with SSA at wavelength 283,3 nm. These results indicate that the optimum initial concentration is 150 mg/L, pH solution is 4, while the particle size is 850 ʮm, temperature of heating the adsorbent is 125 0C, and the flow rate is 20 drops/minute. By using the langmuir adsorption isotherm equation obtained maximum adsorption capacity of the napa metal ions Cd (II) is equal to 0,999 mg/g. The adsorption of metal ions Cd (II) at waste water in Chemical Laboratory Mathematic and saint Faculty UNP has adsorption efficiency 68,72 %.